2015
DOI: 10.1007/s00198-015-3408-3
|View full text |Cite
|
Sign up to set email alerts
|

Serum carcinoembryonic antigen-related cell adhesion molecule 1 level in postmenopausal women: correlation with β-catenin and bone mineral density

Abstract: This study provides evidence that decreased serum CEACAM1 levels are related to low BMD in postmenopausal women, and that serum CEACAM1 levels correlated positively to β-catenin. It suggests that CEACAM1 might influence the canonical Wnt/β-catenin pathway to modulate bone metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Degradation of β-catenin by the destruction complex is a diagnostic pathway from Module 4. Numerous studies have indicated the association between β-catenin and PO ( 41 44 ). In the present study, the diagnostic module-associated pathways were in accordance with the pathological process of PO, which indirectly indicates the feasibility of the application of the present method.…”
Section: Discussionmentioning
confidence: 99%
“…Degradation of β-catenin by the destruction complex is a diagnostic pathway from Module 4. Numerous studies have indicated the association between β-catenin and PO ( 41 44 ). In the present study, the diagnostic module-associated pathways were in accordance with the pathological process of PO, which indirectly indicates the feasibility of the application of the present method.…”
Section: Discussionmentioning
confidence: 99%